The role of inflammation in cardiovascular diseases: the predictive value of neutrophil–lymphocyte ratio as a marker in peripheral arterial disease - Paquissi FC (Dove Medical Press, 2016)
Feliciano Chanana Paquissi Department of Medicine, Clínica Girassol, Luanda, Angola Abstract: Peripheral arterial disease (PAD) is an important manifestation of atherosclerosis, with increasing prevalence worldwide. A growing body of evidence shows that the systemic inflammatory response is closely related to the development, progression, and prognosis of atherosclerosis. In the last decade, several studies have suggested the role of measured inflammatory biomarkers as predictors of severity and prognosis in PAD in an effort to stratify the risk of these patients, to improve treatment selection, and to predict the results after interventions. A simple inflammatory marker, more available than any other, is the neutrophil–lymphocyte ratio (NLR), which can be easily obtained in clinical practice, based on the absolute count of neutrophils and lymphocytes from the differential leukocytes count. Many researchers evaluated vigorously the NLR as a potential prognostic biomarker predicting pathological and survival outcomes in patients with atherosclerosis. In this work, we aim to present the role of NLR as a prognostic marker in patients with PAD through a thorough review of the literature. Keywords: neutrophil–lymphocyte ratio, peripheral arterial disease, inflammation, cardiovascular diseases, biomarkers